Representation of Travel Writing in Gabriel García Márquez’s Un Métier De Rêve: Carl Thompson’s Travel Writing Study - Nurhasanah, Silfi; Sunahrowi, Sunahrowi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2023)
Abstract. Travel writing, a subgenre of literature, depicts a writer's journey in visiting unfamiliar places. The author experienced negotiation between himself and the others about similarities or differences. In the travel writing, a reality is a reference emphasized the most, rather than mere imagination or fiction. This study aims to examine the representation of travel writing in Un Métier de Rêve by Gabriel García Márquez and to uncover the influence of the narrator's personal perspective (the self) on his view of Europeans (the others). The story in short story Un Métier de Rêve is one of Gabriel García Márquez's travel stories included in Douze Contes Vagabonds. This type of research is descriptive-analytic research using literature studies. The data collection technique involves reading, noting, and sorting. In analyzing the data, which includes words, phrases, dialogues, monologues, feelings, and behavior of the characters, the researcher conducted data interpretation by proving or debating a matter through valid evidence using Carl Thompson's travel writing theory, which consists of three concepts, namely: Reporting the World, Revealing the Self, and Representing the Other. The results of the study on Gabriel García Márquez's Un Métier de Rêve show that Márquez seeks to portray the world he encountered rationally and objectively, even the subjective element found in the short story still appears to be objective. As a result, there is an ambiguity found that is uncovered due to the contestation between fact and fiction in travel writing. In addition, the influence of the ideology of the former colonial state apparently provides a particular emphasis on Márquez's strategy in writing his travel stories.  Keywords: Gabriel García Márquez, Travel Writing, Literatur